2015
DOI: 10.5935/1984-2295.20150008
|View full text |Cite
|
Sign up to set email alerts
|

Onion Seedlings Emergence and Initial Growth Under Increased Temperature and CO2

Abstract: Artigo recebido em 10/09/2015 e aceito em 30/11/2015. RESUMOAs mudanças climáticas, especialmente o aumento da temperatura e da concentração de gases de efeito estufa na atmosfera , afetarão o crescimento e desenvolvimento das plantas. O objetivo deste trabalho foi avaliar o efeito de aumento da temperatura e da concentração de CO2 na emergência de plântulas de cebola das cultivares Alfa São Francisco, Franciscana IPA 10, Vale Ouro IPA 11 e Serena. O experimento foi conduzido em câmaras de crescimento, com con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The highest AGS of treatments was 0.13 day -1 of the Vale Ouro IPA 11 genotype and the lowest, 0.11 day -1 of Mata Hari. Costa et al (2015) for a similar temperature situation, they found 0.23 day -1 for cv. Vale Ouro IPA 11.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The highest AGS of treatments was 0.13 day -1 of the Vale Ouro IPA 11 genotype and the lowest, 0.11 day -1 of Mata Hari. Costa et al (2015) for a similar temperature situation, they found 0.23 day -1 for cv. Vale Ouro IPA 11.…”
Section: Discussionmentioning
confidence: 75%
“…Carvalho et al (2015) evaluating the radish (Raphanus sativus) AGT found, for one of the varieties 5.2 days -1 . Costa et al (2015), working with onions from cv. IPA 11 found AGT values of 6.49 at 25ºC and 4.19 at 34ºC.…”
Section: Discussionmentioning
confidence: 99%